Treatment method of lithium-containing glass

By using potassium and fluorine salts in lithium-containing glass for roasting and dissolution processes, the problems of filtration difficulties and environmental pollution in the lithium recycling process in the prior art are solved, and efficient and environmentally friendly lithium resource recycling and utilization are achieved.

CN119800105AActive Publication Date: 2025-04-11CENT SOUTH UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411890551.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-11
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

When the prior art, when recovering lithium from lithium-containing glass waste, there are problems such as adding acid during the leaching process that may produce silica gel, causing difficulty in filtration, difficulty in separation of impurities, and the production of a large amount of wastewater during the pH adjustment of acid leaching and alkali, which pollutes the environment.

Method used

The potassium salt and fluorine salt are used to mix and calcinate with lithium-containing glass. The damage of the Si-O structure by fluoride ions, the intercalation of potassium ions and the deintercalation of lithium ions can be achieved efficient leaching of lithium. The method includes mixing the calcined glass powder with a solution containing Al3+, separating the solid-liquid, then removing impurities, concentrating and precipitating the filtrate, adjusting and decomposing lithium with calcium ions and sodium bicarbonate and other agents, and finally obtaining a compound product of lithium by concentrating the precipitation of lithium.

Benefits of technology

The lithium extraction effect of lithium is improved, the loss of lithium is reduced, the efficient recycling of lithium resources is achieved, and the treatment cost is reduced through the recycling of fluorine, and the pollution of the water environment is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005200550270000011
    Figure HDA0005200550270000011
Patent Text Reader

Abstract

The invention belongs to the field of solid waste resourceful treatment, and relates to a lithium-containing glass treatment method, which comprises: S1, crushing lithium-containing glass to be treated, adding a roasting agent, mixing, and roasting to obtain a clinker; s2, crushing the clinker, mixing the crushed clinker with the dissolution liquid, and performing solid-liquid separation after reaction to obtain filter residues and filtrate; s3, performing impurity removal, concentration and lithium precipitation on the filtrate; the roasting agent is composed of sylvite and villiaumite, the sylvite is one or more of K2SO4, KF, KCl and KNO3, and the villiaumite is one or more of NaF, KF, NH4F and aluminum hydroxyfluoride; the dissolution liquid is a solution containing Al < 3 + >. According to the method, villiaumite and sylvite are adopted for roasting, the purpose of extracting lithium is achieved through intercalation of potassium ions and deintercalation of lithium ions, generated slag is effectively utilized, and the lithium extraction efficiency is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solid waste resource treatment and relates to a method for treating lithium-containing glass. Background Art

[0002] Glass-ceramics usually consists of one or more crystal phases embedded in a glass matrix. Among the various systems in the glass-ceramics family, Li 2 O-Al 2 O 3 -SiO 2 (LAS) glass-ceramics is known for its special thermal expansion properties, which has led to its extensive research and application. 2 O-Al 2 O 3 -SiO 2 (LAS) glass-ceramics mainly consists of Al 2 O 3 、Na 2 O, MgO, K 2 O、SiO 2 Oxides, Li 2 The O content is about 10%. Compared with traditional lithium-containing ore resources such as spodumene, lepidolite, petalite and apatite, it has a simple composition, no toxic or difficult-to-separate elements, and does not react with acids or alkalis at room temperature. If lithium can be efficiently recovered from this type of lithium-containing glass waste and its resource utilization can be realized, it will help alleviate the current shortage of lithium resources.

[0003] Chinese invention patent CN 118326174 A discloses a method for recovering lithium from lithium-containing glass powder, which proposes mixing lithium-containing glass powder with alkaline substances to obtain a mixture; then calcining the mixture at high temperature to obtain a calcined material; mixing the calcined material with acid solution for acid leaching, and obtaining a lithium-containing leaching solution after solid-liquid separation. This invention patent uses alkali calcination to achieve the leaching of valuable lithium in glass powder. However, the addition of acid during the leaching process may cause the generation of silica gel, resulting in difficulty in filtration and impurity separation.

[0004] Chinese invention patent CN 117604271 A relates to a resource treatment method for lithium-containing glass waste, comprising the following steps: pre-treating the lithium-containing glass waste to be treated to obtain powder; uniformly mixing the powder with water-soluble fluoride salt and water to obtain slurry; adding inorganic acid to the slurry, and after the reaction is completed, solid-liquid separation to obtain leachate and leach residue; wherein, during the reaction, the pH value of the slurry is maintained at 0-4 by adding inorganic acid; after adjusting the pH value of the leachate to 5-8 with alkali and / or alkaline solution, solid-liquid separation is performed to obtain purified liquid and cryolite products; after the purified liquid is subjected to lithium precipitation treatment, solid-liquid separation is performed to obtain lithium compound products. However, in the prior art, a large amount of wastewater is generated during acid leaching and alkali pH adjustment, and these wastewaters need to be effectively treated, otherwise they may cause pollution to the water environment, and the subsequent treatment work is large.

[0005] Chinese invention patent CN 118360497 A discloses a method for extracting lithium from spodumene or petalite, and proposes to mix spodumene or petalite with a reconstruction agent by ball mixing to obtain a mixture; the mixture is calcined at 500-1000°C for 0.5-10h and then ball milled to obtain a calcined material; the calcined material is mixed with water or acid and then leached for 0.5-10h, and then solid-liquid separation is performed to obtain a leachate and leached slag. This invention patent uses a method of leaching after calcining fluoride salts and sulfates, thereby achieving the leaching of valuable lithium from spodumene or petalite. However, the generation of LiF in the leached product will result in a low leaching rate and waste of lithium entering the slag phase.

[0006] Chinese invention patent CN 117448593 A relates to a method for recovering lithium from lithium-containing waste, the method comprising the following steps: mixing lithium-containing waste with a roasting additive, and then aerobically roasting the obtained mixed powder; leaching the powder after aerobically roasting, solid-liquid separation, and obtaining a lithium-containing solution; purifying and removing impurities from the obtained lithium-containing solution, and then preparing lithium salt; the roasting additive comprises alkali metal oxide and / or alkali metal fluoride. However, when removing impurities in the prior art, aluminum ions are precipitated in the form of aluminum hydroxide, and lithium loss caused by aluminum hydroxide adsorption causes waste of lithium resources. Summary of the invention

[0007] The object of the present invention is to provide a method for treating lithium-containing glass to improve the lithium extraction effect of the lithium-containing glass.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] A method for treating lithium-containing glass comprises the following steps:

[0010] S1, crushing the lithium-containing glass to be treated, adding a roasting agent, mixing and roasting to obtain a clinker;

[0011] S2, crushing the clinker and mixing it with the dissolving liquid, performing solid-liquid separation after the reaction, and obtaining filter residue and filtrate;

[0012] S3, removing impurities, concentrating and precipitating lithium from the filtrate;

[0013] The calcining agent is composed of potassium salt and fluoride salt, and the potassium salt is K 2 SO 4 , KF, KCl, KNO 3 One or more of the fluoride salts are NaF, KF, NH 4 F. One or more hydroxyaluminum fluorides;

[0014] The dissolving solution contains Al 3+ of solution.

[0015] In one preferred embodiment, the lithium-containing glass comes from one or more of waste electronic product covers, display screens, and defective products and tailings in the deep processing of lithium-containing glass.

[0016] In one preferred embodiment, the lithium-containing glass comprises Al 2 O 3 , Li 2 O and SiO 2 .

[0017] In one preferred embodiment, the lithium-containing glass comprises Li 2 O 5-15 parts, SiO 2 39.5-73.0 parts, Al 2 O 3 0.8-30.0 parts, MgO 0-3.0 parts, Na 2 O 0-2.0 parts, CaO 0.1-0.50 parts, K 2 O 0-0.5 parts, B 2 O 0-2.0 parts.

[0018] In one preferred embodiment, in S1, the lithium-containing glass is crushed to a particle size of less than 100 mesh, preferably less than 150 mesh.

[0019] In one preferred embodiment, the mass ratio of the sintering agent to the lithium-containing glass is 0.5-2:1, for example, 1.2:1 or 1.8:1.

[0020] In one preferred embodiment, the mass ratio of the fluoride salt to the lithium-containing glass is not less than 0.2:1, and the mass ratio of the potassium salt to the lithium-containing glass is not less than 0.3.

[0021] A low fluorine content will result in insufficient destruction of the Si-O structure that locks lithium ions, making it difficult to deintercalate internal lithium ions and reducing the leaching rate; a high fluorine content will cause serious damage to the glass structure, causing a large amount of silicon to enter the solution and generate silica gel during the leaching process, making filtration difficult. Potassium salt mainly plays a replacement role. If the amount of potassium salt is small, the leaching rate of lithium will also be low; if the amount of potassium salt is too high, it will form a glassy state, which is difficult to demold and the leaching rate will also be reduced.

[0022] In one preferred embodiment, in S1, the calcination temperature is 500°C-1000°C, more preferably 700°C-800°C; and the calcination time is 4-8h.

[0023] In one preferred embodiment, in S2, the liquid-to-solid ratio of the dissolution solution to the clinker is 5-20 ml:1 g, preferably 8-15 ml:1 g.

[0024] In one preferred embodiment, in S2, the Al in the dissolution solution 3+ The mass ratio to clinker is 1-4:25, more preferably 2-3:25.

[0025] If the amount of aluminum ions is too little, part of the lithium fluoride will still exist in the slag in the solid phase, resulting in lithium waste; if the amount is too much, the impurity removal process will be too long.

[0026] In one preferred embodiment, in S2, the anions in the dissolution solution include Cl - 、SO 4 2- 、NO 3 - One or more of the .

[0027] In one preferred embodiment, in S2, the dissolving solution is Al 2 (SO 4 ) 3 、AlCl 3 、Al(NO 3 ) 3 、Al 2 (SO 4 ) 3 18H 2 One or more of O.

[0028] In one preferred embodiment, in S2, the reaction temperature is 70-95°C, preferably 90-95°C; and the reaction time is 1-2h.

[0029] In one preferred embodiment, in S3, impurity removal includes three stages of reaction, the first stage of reaction is to remove aluminum and fluorine, the second stage of reaction is to remove fluorine, and the third stage of reaction is to remove calcium.

[0030] In one preferred embodiment, the first stage reaction is: adjusting the pH of the filtrate to 5-7, preferably 6-6.5, and performing solid-liquid separation after the reaction to obtain filter residue C and filtrate D; the reaction temperature is 80-95°C.

[0031] In a preferred embodiment, one or both of KOH and NaOH are used to adjust the pH of the filtrate to 5-7.

[0032] The components of the residue C are mainly aluminum hydroxyfluoride and aluminum hydroxide, and aluminum and fluorine are removed by adjusting the pH.

[0033] In one preferred embodiment, the filter residue C is returned as a roasting agent.

[0034] In one preferred embodiment, the second stage reaction is: adding calcium ions to the filtrate D, performing solid-liquid separation after the reaction, and obtaining filter residue E and filtrate F.

[0035] By adding calcium ions to filtrate D, the F in filtrate F - The concentration was reduced to below 50 ppm.

[0036] In one preferred embodiment, the calcium ions are derived from Ca(OH) 2 , calcium oxide or calcium chloride, any one or more thereof.

[0037] In one preferred embodiment, the third stage reaction is: adding Na 2 CO 3 or sodium bicarbonate, and after the reaction, solid-liquid separation is performed to obtain filter residue G and filtrate H, and the filtrate H is concentrated and lithium is precipitated.

[0038] The method of concentrating precipitated lithium is a common method in the art, and the present invention will not be described in detail here.

[0039] By adding Na 2 CO 3 Ca in the solution 2+ The concentration dropped to below 10ppm.

[0040] In one preferred embodiment, the method for treating lithium-containing glass further comprises: washing the filter residue, filter residue C, filter residue E, and filter residue G with water, and returning the washing liquid after washing to prepare the dissolving liquid.

[0041] The present invention bakes lithium-containing waste glass mixed with a baking agent containing potassium salt and fluoride salt, and achieves the purpose of lithium extraction by destroying the Si-O structure with fluoride ions, embedding potassium ions, and de-embedding lithium ions into the soluble phase for leaching. The equation of the reaction to be generated is as follows:

[0042] F - +LiAlSi4 O 10 →LiF+AlSi 3 O 8 - +SiO 2 ;

[0043] K + +AlSi 3 O 8 - →KAlSi 3 O 8 .

[0044] Based on the combined effect of the two, the efficiency of lithium extraction is improved.

[0045] The filter residue obtained by the present invention can be used as an additive for ceramic materials after washing, drying and grinding; the filter residue C is returned for roasting, the lithium adsorbed in the precipitation process enters the soluble phase again and the water washing liquid of all the filter residues can be returned for the dissolution process, which can effectively reduce the loss of lithium, and the repeated use of fluorine in the whole cycle process can reduce the processing cost.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] (1) When the pH is adjusted, aluminum and fluorine are precipitated in the form of hydroxyaluminum fluoride. The obtained hydroxyaluminum fluoride can be returned as a calcining agent. The lithium loss it carries enters the liquid phase again after being dissolved during calcination, which can effectively reduce the loss of lithium and realize the recycling of fluorine, thereby reducing the processing cost; the leached product does not contain LiF, and the leaching rate is relatively high.

[0048] (2) The entire process of the present invention adopts fluoride salt and potassium salt roasting to achieve the purpose of extracting lithium through the embedding of potassium ions and the deintercalation of lithium ions. All water washing liquids can be returned to construct the dissolution liquid, which effectively reduces the loss of lithium. More importantly, the slag generated in the lithium extraction process can be converted into valuable products, realizing the comprehensive recycling of lithium-containing waste glass, and providing a valuable reference for the effective recycling of lithium resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The present invention is a flow chart of a method for processing lithium-containing glass. DETAILED DESCRIPTION

[0050] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0051] 100 g of lithium-containing waste glass from a panel factory was taken, and the composition (mass fraction wt%) was as shown in Table 1.

[0052] Table 1 Composition of lithium-containing glass

[0053] serial number <![CDATA[Li 2 The]]> <![CDATA[Na 2 The]]> <![CDATA[K 2 The]]> CaO MgO <![CDATA[Al 2 THE 3 ]]> <![CDATA[B 2 The]]> <![CDATA[SiO 2 ]]> 1 10.4464 0.9847 0.1885 0.3370 0.9568 14.2913 0.9656 68.5411 2 9.9236 1.1610 0.2279 0.3770 1.0872 15.1655 0.9981 66.1832

[0054] Example 1

[0055] according to Figure 1 The flowchart shown in the figure is used to process the lithium-containing waste glass from a panel factory, as follows:

[0056] (1) Lithium-containing waste glass from a panel factory was crushed to obtain glass powder with a particle size of less than 150 meshes, the composition of which is No. 1 shown in Table 1;

[0057] (2) The glass powder, potassium sulfate and sodium fluoride are placed in a ball mill in a mass ratio of 1:0.45:0.25 to obtain a mixture.

[0058] (3) The mixed material is placed in a pit furnace and roasted at 700° C. for 5 h. After cooling, the mixed material is ball-milled and passed through a 150-mesh sieve to obtain roasted clinker.

[0059] (4) Take 60g of roasted clinker and mix it with the dissolution solution. 2 (SO 4 ) 3 18H 2 O mass ratio is 1:1, the liquid-solid ratio of the dissolution liquid to the clinker is 5ml:1g, the reaction temperature is controlled at 90℃, the temperature is kept for 1h, the solid-liquid separation is performed, 300ml of leaching liquid and leaching residue are obtained, the leaching residue is washed once, the liquid-solid ratio of the leaching residue to the washing water is 3ml:1g, and 50.08g of washed residue is obtained. The lithium content in the washed residue is tested to be 0.1361%, and the balanced lithium leaching rate is 95.78%.

[0060] (5) Add 2 mol / L NaOH to the leaching solution at a rate of 1 ml / min, control the reaction temperature to 90°C, adjust the pH of the solution to 6.23, separate the solid and liquid to obtain a residue C and a filtrate D, and return the obtained residue C to step (3) as a roasting agent. Add 5 g Ca(OH) 2 After reacting for 30 minutes, solid-liquid separation was performed to obtain residue E and filtrate F. The concentration of Al, F and Li in filtrate F was 6 ppm, 48 ppm and 2.5 g / L, respectively. 10% excess Na 2 CO 3 After the reaction, solid-liquid separation is performed to obtain residue G and filtrate H. The Ca in the filtrate H is2+ The concentration is reduced to 7ppm, and the filtrate H can be used for subsequent lithium concentration and precipitation operations, and the slag produced during the aluminum removal process is returned as a roasting agent.

[0061] After the filter residues C, E and G are washed with water, the solid and liquid are separated to obtain washed residues and washing liquid, and the washing liquid is returned to step (4) together with the washing liquid of step (4) to construct the dissolution solution.

[0062] Example 2

[0063] Example 1 was repeated, except that the mass ratio of glass powder to potassium sulfate and sodium fluoride was adjusted to 1:0.3:0.25, and the balanced lithium leaching rate was 93.66%.

[0064] Example 3

[0065] Example 1 was repeated, except that the mass ratio of glass powder to potassium sulfate and sodium fluoride was adjusted to 1:0.6:0.25, and the balanced lithium leaching rate was 94.30%.

[0066] Comparative Example 1

[0067] Example 1 was repeated, except that the mass ratio of glass powder to potassium sulfate and sodium fluoride was adjusted to 1:0.45:0.1, and the balanced lithium leaching rate was 50.38%.

[0068] Comparative Example 2

[0069] Example 1 was repeated, except that the mass ratio of glass powder to potassium sulfate and sodium fluoride was adjusted to 1:0.18:0.25, and the balanced lithium leaching rate was 77.81%.

[0070] Comparative Example 3

[0071] Take the lithium-containing waste glass from a panel factory and crush it to obtain glass powder with a particle size of less than 150 mesh; place a certain amount of glass powder and potassium sulfate in a ball mill at a mass ratio of 1:0.3 to obtain a mixture, place the mixture in a pit furnace and roast it at 750℃ for 5h, after cooling, ball mill, and pass through a 150-mesh sieve to obtain roasted clinker. Take 60g of roasted clinker and mix it with the dissolution solution. The Al in the clinker and the dissolution solution 2 (SO 4 ) 3 18H 2 The mass ratio of lithium ion to lithium ion was 1:1, the liquid-solid ratio of the dissolution solution to the clinker was 10 ml:1 g, the reaction temperature was controlled at 90 °C, the leaching was kept warm for 1 hour, and the solid-liquid separation was performed. The balanced lithium leaching rate was 37.77%.

[0072] Example 4

[0073] Take the lithium-containing waste glass from a panel factory and crush it to obtain glass powder with a particle size of less than 150 mesh; the composition is as shown in Table 1, No. 2; the glass powder, potassium chloride and sodium fluoride are placed in a ball mill at a mass ratio of 1:0.3:0.4 to obtain a mixture, and the mixture is placed in a pit furnace and roasted at 750°C for 5 hours. After cooling, ball milling, and 150 mesh sieve are obtained to obtain roasted clinker. Take 60g of the roasted clinker and mix it with the dissolution. The Al in the clinker and the dissolution is 2 (SO 4 ) 3 18H 2 The mass ratio of lithium ion to lithium ion was 1:1, the liquid-solid ratio of the dissolution liquid to the clinker was 10 ml:1 g, the reaction temperature was controlled at 90° C., the temperature was kept for 1 hour, and the solid-liquid separation was performed. The equilibrium lithium leaching rate was 98.92%. Others were the same as in Example 1.

[0074] Example 5

[0075] Take the lithium-containing waste glass from a panel factory and crush it to obtain glass powder with a particle size of less than 150 mesh; put the glass powder, potassium fluoride and sodium fluoride in a ball mill at a mass ratio of 1:0.4:0.4 to obtain a mixture, and place the mixture in a pit furnace for roasting at 750°C for 5 hours. After cooling, ball mill, and pass through a 150-mesh sieve to obtain roasted clinker. Take 60g of the roasted clinker and mix it with the dissolution. The Al in the clinker and the dissolution is 2 (SO 4 ) 3 18H 2 O mass ratio is 1:1, the liquid-solid ratio of the dissolution solution to the clinker is 15ml:1g, the reaction temperature is controlled at 95°C, the temperature is kept for 1h, the solid-liquid separation is performed, and the balanced lithium leaching rate is 97.63%. Others are the same as in Example 1.

[0076] Example 6

[0077] Take the lithium-containing waste glass from a panel factory and crush it to obtain glass powder with a particle size of less than 150 mesh; put the glass powder and potassium fluoride in a ball mill at a mass ratio of 1:0.3 to obtain a mixture, and place the mixture in a pit furnace for roasting at 750°C for 5 hours. After cooling, ball mill, and pass through a 150-mesh sieve to obtain roasted clinker. Take 60g of the roasted clinker and mix it with the dissolution. The Al in the clinker and the dissolution 2 (SO 4 ) 3 18H 2 The mass ratio of lithium ion to lithium ion was 1:1, the liquid-solid ratio of the dissolution liquid to the clinker was 20 ml:1 g, the reaction temperature was controlled at 90° C., the temperature was kept for 1 hour, and the solid-liquid separation was performed. The equilibrium lithium leaching rate was 91.12%. Others were the same as in Example 1.

[0078] Comparative Example 4

[0079] Take the lithium-containing waste glass from a panel factory and crush it to obtain glass powder with a particle size of less than 150 mesh; put the glass powder and potassium chloride in a ball mill at a mass ratio of 1:0.3 to obtain a mixture, and place the mixture in a pit furnace for roasting at 750°C for 5 hours. After cooling, ball mill, and pass through a 150-mesh sieve to obtain roasted clinker. Take 60g of the roasted clinker and mix it with the dissolution. The Al in the clinker and the dissolution is 2 (SO 4 ) 3 18H 2 The mass ratio of lithium ion to lithium ion was 1:1, the liquid-solid ratio of the dissolution liquid to the clinker was 10 ml:1 g, the reaction temperature was controlled at 90° C., the temperature was kept for 1 hour, and the solid-liquid separation was performed. The equilibrium lithium leaching rate was 48.55%. Others were the same as in Example 4.

[0080] Comparative Example 5

[0081] Take the lithium-containing waste glass from a panel factory and crush it to obtain glass powder with a particle size of less than 150 mesh; place a certain amount of glass powder and sodium fluoride in a ball mill at a mass ratio of 1:0.4 to obtain a mixture, place the mixture in a pit furnace and roast it at 750℃ for 5h, after cooling, ball mill, and pass through a 150-mesh sieve to obtain roasted clinker. Take 60% of the roasted clinker and mix it with the dissolution solution. The Al in the clinker and the dissolution solution 2 (SO 4 ) 3 18H 2 The mass ratio of lithium ion to lithium ion was 1:1, the liquid-solid ratio of the dissolution liquid to the clinker was 10 ml:1 g, the reaction temperature was controlled at 90° C., the temperature was kept for 1 hour, and the solid-liquid separation was performed. The equilibrium lithium leaching rate was 80.07%. Others were the same as in Example 4.

[0082] Comparative Example 6

[0083] Take the lithium-containing waste glass from a panel factory and crush it to obtain glass powder with a particle size of less than 150 mesh; place a certain amount of glass powder, sodium sulfate and sodium fluoride in a ball mill according to a mass ratio of 1:0.3:0.4 to obtain a mixture, place the mixture in a pit furnace and roast it at 750°C for 5 hours, after cooling, ball mill, and pass through a 150-mesh sieve to obtain a roasted clinker. Others are the same as in Example 4. The balanced lithium leaching rate is 75.25%.

[0084] By comparison, it can be seen that the lithium leaching rate of glass roasted with potassium salt alone is low, and more lithium remains in the slag phase when roasted with fluoride salt alone. Potassium fluoride has relatively good effects due to its simultaneous effects of fluoride ions and potassium ions, but the cost of using potassium fluoride is relatively expensive and there must be an excess of one of the potassium ions or fluoride ions, resulting in waste. After the fluoride ions destroy the Si-O structure, the replacement effect of sodium ions is very poor, and the effect on the lithium leaching rate is very small. Under the same conditions, the leaching rate of lithium by potassium ions has a significant improvement, which is close to complete leaching. In order to maximize the leaching rate of lithium, the mixed roasting of fluoride salt and potassium salt can effectively achieve this goal, and can maximize the atomic utilization rate and thus reduce costs.

[0085] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for treating lithium-containing glass, characterized in that: The steps include: S1, crushing the lithium-containing glass to be treated, adding a roasting agent, mixing and roasting to obtain a clinker; S2, crushing the clinker and mixing it with the dissolving liquid, performing solid-liquid separation after the reaction, and obtaining filter residue and filtrate; S3, removing impurities, concentrating and precipitating lithium from the filtrate; The calcining agent is composed of potassium salt and fluoride salt, wherein the potassium salt is one or more of K2SO4, KF, KCl, and KNO3, and the fluoride salt is one or more of NaF, KF, NH4F, and hydroxyaluminum fluoride; The dissolving solution contains Al 3+ of solution.

2. The processing method according to claim 1, characterized in that: The lithium-containing glass includes Al2O3, Li2O and SiO2.

3. The processing method according to claim 1, characterized in that: The mass ratio of the sintering agent to the lithium-containing glass is 0.5-2:

1.

4. The processing method according to claim 1, characterized in that: The mass ratio of fluoride salt to lithium-containing glass is not less than 0.2:1, and the mass ratio of potassium salt to lithium-containing glass is not less than 0.

3.

5. The processing method according to claim 1, characterized in that: In S1, the calcination temperature is 500°C-1000°C, and the calcination time is 4-8h.

6. The processing method according to claim 1, characterized in that: In S2, the liquid-to-solid ratio of the dissolution liquid to the clinker is 5-20ml:1g; the Al in the dissolution liquid 3+ The mass ratio to clinker is 1-4:

25.

7. The processing method according to claim 1, characterized in that: In S2, the dissolving solution is Al2(SO4)3, One or more of AlCl3, Al(NO3)3, Al2(SO4)3·18H2O.

8. The processing method according to claim 1, characterized in that: In S2, the reaction temperature is 70-95°C; The reaction time is 1-2h.

9. The processing method according to any one of claims 1 to 8, characterized in that: In S3, impurity removal includes three stages of reaction. The first stage of reaction removes aluminum and fluorine, the second stage of reaction removes fluorine, and the third stage of reaction removes calcium.

10. The processing method according to claim 9, characterized in that: The first stage reaction is: adjusting the pH of the filtrate to 5-7, and performing solid-liquid separation after the reaction to obtain filter residue C and filtrate D; the second stage reaction is: adding calcium ions to the filtrate D, and performing solid-liquid separation after the reaction to obtain filter residue E and filtrate F; the third stage reaction is: Na2CO3 or sodium bicarbonate is added to the filtrate F, and solid-liquid separation is performed after the reaction to obtain filter residue G and filtrate H, which is then concentrated to precipitate lithium.

Citation Information

Patent Citations

  • Method for recovering lithium from lithium-containing waste

    CN117448593A

  • Method for extracting lithium from spodumene or petalite

    CN118360497A

  • Method for recovering lithium from lithium-containing aluminum electrolyte

    CN115011798A

  • Recycling treatment method of lithium-containing glass waste

    CN117604271A

  • Method for recovering lithium from waste glass powder

    CN118166218A